Customized Preliminary Impression: A Novel Impression Technique for Severely Resorbed Edentulous Ridges - Arpit Sikri; Jyotsana Sikri; Tarun Kalra; Ritika Sharda; Natasha Bathla; Sahil Thakur (Sudan Journal of Medical Sciences)
Patients with long-term edentulism and/or ill-fitting (poorly fitted) dentures are more likely to experience severe mandibular alveolar ridge resorption. Some of these patients have genial tubercles that rise over the mandibular residual ridge in the anterior region and protrude into the floor of the mouth. Typically, the most prominent portions of the resorbed mandibular edentulous ridge are in contact with the lingual flanges of the mandibular stock impression trays (i.e., genial tubercles and internal oblique lines). In these situations, it is advised that a preliminary custom impression tray be created to pour an initial impression, allowing for the fabrication of individual custom trays. In general, dental practice for the fabrication of the complete denture, the stock trays are used for making the preliminary impression and the custom trays for the final impression. The present article portrays an innovative and efficient clinical technique involving the fabrication of a customized preliminary impression tray for preliminary impression making particularly in unconventional situations, that is, pronounced mandibular alveolar ridge resorption.